1971
DOI: 10.1039/c29710001129
|View full text |Cite
|
Sign up to set email alerts
|

New bromo-pyrrole derivatives from the sponge Agelas oroides

Abstract: The sponge Agelas oroides contains 4,5-dibromopyrrole-2-carboxylic acid (4), the corresponding nitrile and amide; oroidin contains an amide derived from (4) and a substituted 2-aminoimidazole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
135
0
4

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(141 citation statements)
references
References 0 publications
2
135
0
4
Order By: Relevance
“…[1][2][3][4][5][6][7] Historically, these compounds, which have been found only in the marine environment to date, have attracted the attention of natural product chemists because of their structural complexity. Today, the interest is sparked not only by the wide structural diversity, ranging from simple molecules like oroidin 8,9 to complex structures like palau'amine 10,11 and stylissadine A and B, 12 but also by their organic synthesis, 13 bio-synthesis, 14 and pharmacological activities. 6,7,15 Furthermore, these compounds have a chemo-ecological interest due to their role in chemically mediated interactions such as in the chemical defense against predators 16,17 and fouling organisms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Historically, these compounds, which have been found only in the marine environment to date, have attracted the attention of natural product chemists because of their structural complexity. Today, the interest is sparked not only by the wide structural diversity, ranging from simple molecules like oroidin 8,9 to complex structures like palau'amine 10,11 and stylissadine A and B, 12 but also by their organic synthesis, 13 bio-synthesis, 14 and pharmacological activities. 6,7,15 Furthermore, these compounds have a chemo-ecological interest due to their role in chemically mediated interactions such as in the chemical defense against predators 16,17 and fouling organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The methanol extract of the sponge yielded 0.1 g of Fr A, 1.7 g of Fr B, 5.5 g of Fr C and 3.2 g of Fr D. Fraction B (310 mg) was chromatographed on Sephadex LH-20 (MeOH), C, 8 reversed phase (MeOH-H~O 0/100 to 100/0) and silica gel (CHCI3-MeOH-NH 3 25% 10/3/1) successively. This yielded 28 (Nakamura et al, 1984c;Kobayashi et al, 1986b) and 16 (Forenza et al, 1971) identified on the basis of their spectral properties (IR, UV, 1H and ~3C NMR). Moreover, TLC of Fr B showed the presence of 29.…”
Section: Introductionmentioning
confidence: 99%
“…4). Nagelamide W (9) (6) and Nagelamides U-W (7)(8)(9) might be biogenetically generated by the addition of guanidine to oroidin.…”
Section: Monomeric Bromopyrrole Alkaloids Agelamadin F and Nagelamidmentioning
confidence: 99%
“…15) As part of that research project, bromopyrrole alkaloids in sponges Agelas spp. (SS-162, SS-307) were investigated, resulting in the isolation of 18 unique alkaloids including five dimeric bromopyrrole alkaloids (1-5), ten monomeric bromopyrrole alkaloids (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), and three conjugates of monomeric bromopyrrole alkaloid and hydroxykynurenine (16)(17)(18). In this mini-review, we describe the isolation, structure elucidation, and antimicrobial activities of these alkaloids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation